Agricultural value chains and structural transformation in Senegal: A product space approach - Ulimwengu, John M.; Savadogo, Kimsey; Sall, Leysa M.; Faye, Amy; Dia, Khadim (2019)
Using the product-space approach and BACI dataset for the period 1995-2014, we analyze the role of agricultural value chains selected under Agricultural Policy Support Project (PAPA) in Senegal’s structural transformation process. Overall, our findings suggest that the dynamics of economic complexity index (ECI) has been rather volatile throughout the period. Simulations results suggest that exporting only non-processed agricultural products, even with Revealed Comparative Advantage (RCA), is not enough to substantially boost the country structural transformation process. Exporting manufacturing products with RCA is by far the best option to fast-track structural transformation. However, a value chain approach like the one adopted by PAPA where the production and processing capability are promoted, has the potential to trigger an agriculture-driven structural transformation. We also found that diversity (increase of exported products with RCA) alone does not generate structural transformation which requires also sophistication (adding value to primary goods). It follows that to create a critical mass of agriculture-led transformational activities, the country must: i) modernize smallholders’ agribusiness value chains; ii) integrate smallholder farmers into transforming value chains; iii) optimize the role of producer organizations in promoting the integration of smallholders into agricultural value chains; iv) improve market intermediation, financial services and technology innovation.